IDENTIFIKASI RISIKO KRITIS KAPAL TENGGELAM MENGGUNAKAN METODE ANALISIS RISIKO - Shanty Yahya; Puji Astuti Amaliah; Roni Katily (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The increase in trade flows has a positive impact on the growth of the shipping industry. However, this growth is not in line with the quality of shipping safety. The high number of ship accidents causes low safety quality. Efforts to prevent ship accidents have been made to reduce the number of ship accidents, but ship accidents in Indonesian waters still occur because the identification of the cause of the accident is not accurate yet. This research aims to identify the Risk Agent of sinking ships in the critical category, so that preventive action can be implemented appropriately. This research uses the method of the House of Risk Phase 1 for risk assessment and identifying critical risks of sinking ship. This research identifies that the Risk Agent in critical category consist of the ship’s crew did not make stability calculation after loading, Harbormaster and ship’s crew did not inspection of the quantity of cargo after loading, stowage plan does not match the cargo arrangements on the ship, there is no ship stability check, and there is no inspection of the technical condition of the ship’s plates. The cause of the sinking ship was dominated by loading cases.